Excise taxation to manage electricity problem in Thailand - Assavinprecha, Chayaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The purposes of this research intended to study the objective of this research are to study: 1. Study on the concepts and reasons of the European Union excise duty on Electrical Energy 2. Study on the structure of the excise taxation in Thailand 3. Study on the use of excise taxation of electricity in Thailand compare to European Union excise duty on Electrical Energy Research Methodology is qualitative research. Data was gathered from relevant laws, such as the Council Directive 2003/96/EC – Energy Taxation Directive and the Excise Tax Act, BE 2560 (2017), and published literature on mixed form excise tax collection structure to analyze and resolve issues. The research results revealed as follows: 1. The European Union Directive that uses for electrical excise duty is Council Directive 2003/96/EC – Energy Taxation Directive. The important purposes of the electricity excise tax are to ensure the proper functioning of the internal market as regards the taxation of energy products and electricity and Taxation related to CO2 emissions can be a cost-effective means for the Member States to achieve the reductions of greenhouse gasses necessary 2. The Thai law that uses for excise duty is the Excise Tax Act, BE 2560 (2017). Amend the old 7 laws into the Excise Tax Act, BE 2560 (2017). 3. The concepts and reasons for the European Union excise duty on electrical energy can be used in Thailand. By implement reform on the Thai excise tax, in this case, is the Excise Tax Act, BE 2560 (2017). for the proposal to maintain the balance between electricity supply and demand. Article history : Received 21 June 2019 Revised 21 July 2019 Accepted 25 July 2019 SIMILARITY INDEX = 0.00 %